EVALUATION OF THE MITOCHONDRIA RESPIROMETRIC FUNCTION IN THE CONDITIONS OF PATHOLOGIES OF VARIOUS GENESES - A. V. Voronkov; D. I. Pozdnyakov; S. A. Nigaryan; E. I. Khouri; K. A. Miroshnichenko; A. V. Sosnovskaya; E. A. Olokhova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2019)
The aim of the paper is to assess the change in the mitochondrial respirometric function under conditions of various pathologies.Materials and methods. The study was performed on male Wistar rats. Experimental focal cerebral ischemia, traumatic brain injury, coronary occlusive myocardial infarction and muscle dysfunction were used as pathological models. Focal ischemia was reproduced by the method of irreversible thermocoagulation of the middle cerebral artery. Traumatic brain injury was modeled by the method of free fall of the load. Experimental myocardial infarction was reproduced by ligating the descending branch of the left coronary artery. Muscle dysfunction was modeled by the method of «forced swimming with a 20% burden». The respiratory function of mitochondria was assessed by the method of respirometry by the change in oxygen consumption when introducing mitochondrial respiration into the medium: Oligomycin, Rotenone and FCCP. Additionally, we evaluated the intensity of the glycolysis process and the activity of respiratory complexes I, II, IV and V. In order to comprehensively assess the respiratory function, an ELISA study was conducted to determine the concentration of ATP, mitochondrial ATP synthetase, cytochrome C oxidase and NADP-Oxidase 4.Results. In the course of the study it was established that under conditions of experimental cerebral ischemia, traumatic brain injury, myocardial infarction and muscle dysfunction, the ATP-generating ability of mitochondria the maximum breathing and respiratory capacity deteriorated, herby the decrease in overall respiratory function was accompanied by an increase in glycolysis, which was uncompensated, as well as dysfunction of mitochondrial complexes I, II, IV and V, confirmed by an increase in NADPH oxidase 4 activity and a decrease in cytochrome C oxidases and ATP synthetase. As a result, the observed changes in mitochondrial respiration function contributed to a decrease in ATP concentration under conditions of cerebral ischemia - by 3.2 times (p <0.05), traumatic brain injury - by 2.6 times (p <0.05), myocardial infarction - by 1.8 times (p <0.05) and muscle dysfunction - by 4 times (p <0.05).Conclusion. Basing on the data obtained, we can assume that in conditions of cerebral ischemia, traumatic brain injury, myocardial infarction and muscle dysfunction, there is deterioration of the mitochondrial respirometric function with inhibition of ATP synthesis and increased glycolysis.